Case-study analysis of concrete large-panel apartment building at pre- and post low-budget energy-renovation. Issue 1 (2nd January 2017) - Kuusk, Kalle; Kalamees, Targo; Link, Siim; Ilomets, Simo; Mikola, Alo
Abstract: The paper presents a case study analysis of low-budget renovation of a typical concrete large-panel apartment building. Focus is on the measurements and analyses of energy consumption, indoor climate, CO2 concentration, air leakage rate, thermal transmittance of thermal bridges, and thermal transmittance of the building envelope before and after the renovation. Results indicate that the renovation project was generally successful, with delivered energy need decreasing by 40% and heating energy need decreasing by 50%. However, some key problems need to be solved to achieve full energy efficiency potential of the renovation works. Those critical problems are the performance (thermal comfort, heat recovery) of ventilation systems, thermal bridges of external wall/window jamb and economic viability. Currently, a major renovation is not economically viable, therefore financial assistance to the apartment owners' associations is required to encourage them to undertake major renovations.